TO THE QUESTION OF MANAGING VALUE COMPANY WITHIN THE CONCEPT OF SUSTAINABLE ECONOMIC DEVELOPMENT - Elena I. Pavlova; Elena Ya. Sinicyna (Статистика и экономика, 2016)
ARTICLE RETRACTED The article presents the study of identifying the impact of compliance with principles of sustainable development in the market value of the com-pany. The methods of determining the level of sustainable development of companies. The urgency of following the concept of sustainable develop-ment of enterprises. The method of determining the impact of sustainable development indicators in the reputational value of the company.